SENTINEL-2-BASED WATER QUALITY DYNAMICS IN SARYGAMYSH LAKE: A REMOTE SENSING ASSESSMENT - Ismoilova Umida (SPAIN- SCIENTIFIC REVIEW OF THE PROBLEMS AND PROSPECTS OF MODERN SCIENCE AND EDUCATION, 2025)
Sarygamysh Lake, a crucial anthropogenic terminal reservoir in Central Asia, is ecologically and hydrologically stressed due to its reliance on polluted agricultural drainage and recent severe water deficits. This study employs the Sentinel-2 Water Quality (Se2WaQ) script within the Google Earth Engine  environment to monitor the yearly dynamics of key Optically Active Water Quality Parameters (OAPs) between 2017 and 2025. The analysis, leveraging the script's empirical models for Chlorophyll-a, Cyanobacteria, Turbidity, Colored Dissolved Organic Matter (CDOM), Salinity index and Water Color (Color), provides critical spatio-temporal insights into the lake's ecological response to drought and continuous pollutant inflow. The objective is to establish an up-to-date baseline for water quality trends, which is essential for regional water management and conservation efforts.